Aneks . no. 10, 1981 - Niezależne Zrzeszenie Studentów WSP Opole, [ed. Mirosław Olszewski et al.] (NZS WSP, 1981)
Creation and circulation: After the introduction of the Martial Law publication suspended in 1982-1987. Republished in December 1988